2006
DOI: 10.1021/jp054178p
|View full text |Cite
|
Sign up to set email alerts
|

Single Molecule Spectroscopy Studies of Diffusion in Mesoporous Silica Thin Films

Abstract: Single molecule spectroscopy is applied in studies of diffusion and surface adsorption in sol-gel-derived mesoporous silica thin films. Mesoporous films are obtained by spin casting surfactant-templated sols onto glass substrates. Small-angle X-ray diffraction results are consistent with hexagonally ordered mesophases in as-synthesized (i.e., surfactant-containing) films. Upon calcination, a 30% contraction and disordering of these structures occurs. Nile Red is used as a fluorescent probe of both the as-synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
125
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(137 citation statements)
references
References 54 publications
11
125
1
Order By: Relevance
“…also done by Higgins et al In early studies, they investigated the nanoscale properties, the heterogeneity, and the diffusion behavior of dye molecules in dense (organically modified) sol-gel silica films at the single molecule level [64 -67]. Later, Fu et al [68] and Ye et al [69] extended the approach to porous silica thin films. By incorporating fluorescent dyes into the surfactant phase of the mesoporous silica thin films and comparing their diffusional movement to that of dye molecules loaded into template-free films after calcination, striking differences in the dynamics could be observed.…”
Section: Diffusion In Thin Silica Filmsmentioning
confidence: 99%
“…also done by Higgins et al In early studies, they investigated the nanoscale properties, the heterogeneity, and the diffusion behavior of dye molecules in dense (organically modified) sol-gel silica films at the single molecule level [64 -67]. Later, Fu et al [68] and Ye et al [69] extended the approach to porous silica thin films. By incorporating fluorescent dyes into the surfactant phase of the mesoporous silica thin films and comparing their diffusional movement to that of dye molecules loaded into template-free films after calcination, striking differences in the dynamics could be observed.…”
Section: Diffusion In Thin Silica Filmsmentioning
confidence: 99%
“…Even if the channel dimensions in micro-or mesoporous materials are well below the diffraction limit, useful information can be retrieved by analyzing the diffusion trajectories of individual molecules or by studying correlation in a single-point fluorescence time transient (57). For a terrylenediimide dye diffusing in a mesostructured molecular sieve, it was possible to prove the existence of two subpopulations, one containing mobile dye molecules, and a minor fraction of stationary molecules, which could be assigned to ''dead ends,'' e.g., in collapsed pores, or to strong sorption sites (55).…”
Section: Time Resolution and Dynamicsmentioning
confidence: 99%
“…1, [12][13][14] Martin and co-workers 1, 12 have studied the diffusivity inside nanopores by observing the mass transport across nanopore membranes. In their studies, they estimated the apparent diffusion coefficients of phenol derivatives in columnar alumina pores modified with octadecyltrimethoxysilane; the order of the estimated values was 10 -8 to 10 -6 cm 2 s -1 .…”
Section: Introductionmentioning
confidence: 99%
“…12 For the alumina membrane system, the diffusion coefficients of metal cations (10 -7 to 10 -6 cm 2 s -1 ) in unmodified alumina pores were reported and the surface effect on the diffusion behavior was discussed. 13 Fu et al 14 applied single-molecule fluorescence correlation spectroscopy to estimate an apparent diffusion coefficient of Nile Red in a surfactant-templated mesoporous silica thin film, and found that the diffusion coefficient was very small (∼10 -10 cm 2 s -1 ). These reported diffusion coefficients in nanopores are smaller than those in the bulk solution phase (∼10 -6 cm 2 s -1 ), and this slow diffusivity has sometimes been ascribed to the adsorption of molecules at the inner wall of a nanopore.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation